Chapter The role of Scientific divers in the ADRIREEF project: ARPA Puglia activities - De Gioia, Michele (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The ADRIREEF project was targeted to valorization of the natural and artificial reefs in the Adriatic Sea according to the principles of the Blue Growth. ARPA Puglia identified the coralligenous reef in the Torre Guaceto MPA (Brindisi, Italy) as a case study for the project purposes. According to the project objectives, the Agency selected some low-impact monitoring methods, like a standard photographic sampling method for the benthic communities and the visual census method to describe the fish assemblages and finally a R.O.V. to test the applied methods and compare the obtained data.